Corporate image of zakat institutions in Malaysia - Ab Hamid, Siti Ngayesah; Wan Jusoh, Wan Jamaliah (Universiti Kebangsaan Malaysia, 2016)
The privatization of several zakat institutions in Malaysia has opened a new phase in zakat administration with the aim of improving institutional image, especially through the introduction and implementation of corporate values. Various activities and promotional efforts were undertaken to achieve this objective incurring significant expenditures which would be wasted if they fail to achieve the intended goals. In this light, this study was conducted to identify factors that shape and determine the image of zakat institutions among zakat contributors and noncontributors. Based on the two basic components of corporate image which consisted of emotional and functional components, four factors were proposed – reputation, corporate communication, access to service and contact personnel. A total of 225 questionnaires were administered and analyzed using multiple regression analysis. The findings revealed that reputation and contact personnel had a significant relationship with image. These findings have broadened understanding of the concept of image and its antecedents in the context of zakat institutions in Malaysia.